Bhāratīya rāshṭra nirmātā, yā, Bhāratīya netāoṃke jīvana caritra : sacitra - Siṅghaī, Pannālāla (SAMP early 20th-century Indian books project, 1917)
Biographical sketches of various nationalists and freedom fighters of India.